Public involvement in health research systems: a governance framework - Fiona Alice Miller; Sarah J. Patton; Mark Dobrow; Whitney Berta (BMC, 2018)
Abstract Background Growing interest in public involvement in health research has led to organisational and policy change. Additionally, an emerging body of policy-oriented scholarship has begun to identify the organisational and network arrangements that shape public involvement activity. Such developments suggest the need to clearly conceptualise and characterise public involvement in health research in terms of governance. Methods We drew on an established health research system framework to analyse governance functions related to public involvement, adapting scoping review methods to identify evidence from a corpus of journal papers and policy reports. We drew on the logics of aggregation and top down configuration, using a qualitative interpretive approach to combine and link findings from different studies into framework categories. Results We identified a total of 32 scholarly papers and 13 policy reports (n = 45 included papers) with relevance to governance for public involvement. Included papers were broadly consonant in identifying the need for activity to specify and support public involvement across all four governance functions of stewardship, financing, creating and sustaining resources, and research production and use. However, different visions for public involvement, and the activity required to implement it and achieve impact, were particularly evident with respect to the stewardship function, which seeks to set overall directions for research while addressing the potentially competing demands of a system's many constituents. Conclusions A governance perspective has considerable value for public involvement in health research systems, supporting efforts to coordinate and institutionalise the burgeoning public involvement enterprise. Furthermore, it highlights challenges for what is, ultimately, a highly political intervention, suggesting that diverse publics must be both involved within health research systems and enrolled as governors of them.